Humanistic Psychology Study of Abraham Maslow on the Main Character in Tiba Sebelum Berangkat Novel by Faisal Oddang - Lestari, Sendika; Waluyo, Herman J; Wardani, Negraheni Eko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This article aims to analyze the main character in the novel Tiba Sebelum Berangkat by Faisal Oddang using the humanistic psychology approach of Abraham Maslow. The method used in this research was descriptive qualitative research method. The data source used was Tiba Sebelum Berangkat novel by Faisal Oddang. The data analysis technique in this study used the content analysis. The results of this study indicated that the main character in the novel Tiba Sebelum Berangkat by Faisal Oddang had and performed actions that can be analyzed by using Abraham Maslow's hierarchy of needs. This was shown by the content of the novel which presented about conflicts around human life; beliefs, religions, gender and love. Tiba Sebelum Berangkat novel tried to reflect on what might actually happen in people's real life in South Sulawesi. Based on the novel content, the main character built in the novel performed certain actions in obtaining multilevel needs that must be fulfilled as human beings. Tiba Sebelum Berangkat novel showed how humans obtained multilevel needs that must be fulfilled until human self-actualization was achieved.